Effects of Personal Traits on Generation Y Consumers’ Attitudes Toward the Use of Mobile Devices for Communication and Commerce - Kim, Jihyun; Hahn, Kim (Human Technology, 2012)
The purpose of this study was to investigate the effects of young adult consumers’ personal traits (high-tech involvement, experiment proclivity, and fashion/brand leadership) on their perceptions of and attitudes toward using mobile devices for communications and commerce. The integrated stimulus-organism-responses paradigm (Fiore & Kim, 2007) served as the overarching framework, combining the uses and gratifications theory (Blumler & Katz, 1974) and the extended technology acceptance model (Kim, Ma, & Park, 2009). A convenience sample of 504 college students in 2 U. S. universities provided usable responses to our survey. Causal modeling analysis results showed that personal trait variables had significant impacts on the perceived ease of use, usefulness, and enjoyment, and attitudes toward mobile communication and mobile commerce. Findings also suggested that three perception variables positively influenced attitudes toward using mobile devices for communication as well as for commerce. This study provides empirical evidence of the potential of mobile commerce among young adult consumers.